1979
DOI: 10.2136/sssaj1979.03615995004300030015x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Burning on Chaparral Soils: I. Soil Nitrogen

Abstract: Undisturbed moist or dry soil slabs collected from beneath chaparral plants were burned at different intensities in the laboratory. Inorganic and organic nitrogen levels were measured before and after burning. An intense burn over dry soil slabs decreased KCl‐extractable NH4+‐N in the litter but increased it in the underlying soil. In contrast, NO3‐‐N was decreased in both soil and litter during an intense burn over dry soil. Little change in NO3‐‐ and NH4+‐N occurred when litter and soil were moist. About 67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
2
5

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 0 publications
5
58
2
5
Order By: Relevance
“…The fire-induced increase of available cations observed in the burnt plots were in accordance with the results of DeBano et al (1979) and Trabaud (1983) with burnt soils, and also with those of Fassbender (1975) for Ca, Mg and Na in oven-heated soils. This effect is probably due to the accumulation of ashes rich in oxides and carbonates of basic ions that have been reported by several authors (Chandler et al, 1983;Kutiel et al, 1990;Carballas, 1997), and also to the cations (especially Na) supplied by the fire fighting chemicals.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The fire-induced increase of available cations observed in the burnt plots were in accordance with the results of DeBano et al (1979) and Trabaud (1983) with burnt soils, and also with those of Fassbender (1975) for Ca, Mg and Na in oven-heated soils. This effect is probably due to the accumulation of ashes rich in oxides and carbonates of basic ions that have been reported by several authors (Chandler et al, 1983;Kutiel et al, 1990;Carballas, 1997), and also to the cations (especially Na) supplied by the fire fighting chemicals.…”
supporting
confidence: 89%
“…The NH 4 + -N increase that takes place just after the fire in all burnt soil treatments is a common tendency of recently heated or burnt soils (DeBano et al, 1979;Chandler et al, 1983;Prieto-Fernández et al, 1993). As has previously been mentioned, differences in NH 4 + -N content compared with the US were significant for all soils treated with fire fighting chemicals, but the extremely high concentration of BS+Ap was very likely due to the NH 4 + -N supplied by the ammonium polyphosphate.…”
mentioning
confidence: 99%
“…As in the case of soil organic C, organic N content significantly decreased in the burned soil ( Table 2). The the level of total N, when soil and layers of organic residues remain wet less than 25% of total soil N is lost (DeBano et al 1979). In this study, high soil water content (Table 2) could account for the low percentage of N losses.…”
Section: Experiments IImentioning
confidence: 64%
“…Due to forest clearance lower total N content in soil was reported by several authors from different parts of the world (Girma 1998;Jing-cheng et al 2004). DeBano et al (1979) reported that losses of soil N can occur when heated to temperature as high as 100 o C, which may happen during burning associated with shifting cultivation. Significant increase in available Ca and Mg of the preset study compared to forest land in most of the locations was in agreement with Gafur et al (2000), who also reported an increase of the two elements in shifting cultivated soil than mixed planted forest land in Banderban district.…”
Section: Discussionmentioning
confidence: 99%